A universal DNA microarray for rapid fish species authentication - Patrizia Bade; Sebastian Stix; Kristina Kappel; Jan Fritsche; Ilka Haase; Andrew Torda; Nils Wax; Markus Fischer; Dirk Brandis; Ute Schröder (Food Chemistry: Molecular Sciences)
DNA microarrays are now used in fields such as gene expression analysis, pathogen/virus detection and identification of biomarkers. Although they have been used in the food sector for species identification, they detect a limited number of species and are thus less suited for fishery products due to the large variety of traded species. Here, the aim of this proof-of-principle study was to design a universal DNA microarray that should be able to distinguish all fish species by comparing hybridization signal patterns from samples with patterns obtained from reference specimens. A universal set of 100 DNA probes (based on the genetic marker genes 16S ribosomal RNA and cytochrome b) generated species-specific DNA probe patterns for all 86 analyzed fish specimens. This new screening method shows potential to authenticate specimens from all fish species and by this could play an important role in fighting fraudulent practices and adulteration in the seafood sector.